Revealing the intrinsic connection between residual strain distribution and dissolution mode in Mg-Sc-Y-Ag anode for Mg-air battery - Wei-li Cheng; Xu-bang Hao; Jin-hui Wang; Hui Yu; Li-fei Wang; Ze-qin Cui; Cheng Chang (Journal of Magnesium and Alloys)
The dominated contradiction in optimizing the performance of magnesium-air battery anode lies in the difficulty of achieving a good balance between activation and passivation during discharge process. To further reconcile this contradiction, two Mg-0.1Sc-0.1Y-0.1Ag anodes with different residual strain distribution through extrusion with/without annealing are fabricated. The results indicate that annealing can significantly lessen the “pseudo-anode” regions, thereby changing the dissolution mode of the matrix and achieving an effective dissolution during discharge. Additionally, p-type semiconductor characteristic of discharge product film could suppress the self-corrosion reaction without reducing the polarization of anode. The magnesium-air battery utilizing annealed Mg-0.1Sc-0.1Y-0.1Ag as anode achieves a synergistic improvement in specific capacity (1388.89 mA h g-1) and energy density (1960.42 mW h g-1). This anode modification method accelerates the advancement of high efficiency and long lifespan magnesium-air batteries, offering renewable and cost-effective energy solutions for electronics and emergency equipment.